2003
DOI: 10.1300/j015v26n03_06
|View full text |Cite
|
Sign up to set email alerts
|

Prostitution and the Invisibility of Harm

Abstract: The harm of prostitution is socially invisible, and it is also invisible in the law, in public health, and in psychology. This article addresses origins of this invisibility, how words in current usage promote the invisibility of prostitution's harm, and how public health perspectives and psychological theory tend to ignore the harm done by men to women in prostitution. Literature which documents the overwhelming physical and psychological harm to those in prostitution is summarized here. The interconnectednes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 50 publications
(43 reference statements)
1
52
0
5
Order By: Relevance
“…Findings from a United States study indicated that street workers often exhibit "a kind of invincibility toward 'risk' factors" (Belcher & Herr, 2005, p. 118; see also Farley, 2003). Researchers in a British study concluded that sex workers "construct a continuum of risk" (Sanders, 2004, p. 557; see also Jackson et al, 2007, p. 266).…”
Section: Discussion: Managing Risk In Sex Workmentioning
confidence: 99%
“…Findings from a United States study indicated that street workers often exhibit "a kind of invincibility toward 'risk' factors" (Belcher & Herr, 2005, p. 118; see also Farley, 2003). Researchers in a British study concluded that sex workers "construct a continuum of risk" (Sanders, 2004, p. 557; see also Jackson et al, 2007, p. 266).…”
Section: Discussion: Managing Risk In Sex Workmentioning
confidence: 99%
“…1 Universiti Tunku Abdul Rahman, Kajang, Selangor, Malaysia women have allowed the commodification of women to "sex objects" (Farley, 2003;Dworkin, 1992;MacKinnon, 1989). On the other end of the spectrum, feminist scholars argue for the "right" to capitalize on their sexuality for economic gains.…”
Section: Research-article2016mentioning
confidence: 99%
“…According to Farley (2003) and Harding (2003), moral and political outlooks of feminist groups have inspired members of social sciences and biology to come up with critical questions about the process of traditional research, such as to include aspects of gender, relationship within or between the social world and the natural environment. In fact, some supporters of feminism, such as Ruth Hubbard and Evelyn Fox Keller criticized traditional scientific discourse because history tends to emphasize the male perspective (Blain et al 1990;Freedman, 2003).…”
Section: Epistemology Of Ecofeminism's Struggle For Environmental Manmentioning
confidence: 99%